PERAN ANAK DALAM PEMBANGUNAN EKONOMI - Buchori, Nur S. (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
This paper describes the role of children in economic development. The author tries to explain about the value of children and economic development are discussed by Peter H. Lindert in his book "Child Costs and Economic Development" as well as add some source other than demography researchers about the role of children in the perspective of economic development through the approach to child labor force participation. From this paper can be seen that the role of children in economic development has a close relationship. That the cost of child affect fertility and fertility influence child development. Ie the higher the population growth increasingly affect the rate of economic growth. Increased levels of economic development also has an impact on lowering fertility rates.